Enseñanza de las ciencias morfológicas en ingresantes a la Facultad de Ciencias Naturales y Museo de la UNLP - Camino, Nora Beatriz (2012)
The public University in La Plata from the beginning, tried to analyze and elucidate the theme of failure and dropout in the first years of university life, where such factors ranging psychological, sociological, economic, organizational or due to student interaction and the institution.\nSince 1968 is assigned a value to the social composition of entrants as another factor involved. While it is a subject that was always present, not many studies. The course General Zoology statistically treated the situation of four cohorts of students in first year of the Bachelor in Biology, with the following results: 47.22% (2008), 51.76% (2009), 50. 66% (2010) and 51.61% (2011) of students who drop out of race. Extrapolating a series of variables that play for the college dropout: Variables indicative of prior education and counseling received by the student demographic variables and personal students, variables indicating the student’s employment status and variables related to characteristics of their parents.\nThese variables influence independently or in an interrelated manner. From this theme, since 2009 is implemented in the FCNyM the tutorial system. It is expected that over time, this kind of support is accepted and profited massively by the students, making the increase in retention due to the neutralization of any of the above variables.